2011
DOI: 10.1073/pnas.1104703108
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 from Escherichia coli collaborates with the DnaK chaperone system in client protein remodeling

Abstract: Molecular chaperones are proteins that assist the folding, unfolding, and remodeling of other proteins. In eukaryotes, heat shock protein 90 (Hsp90) proteins are essential ATP-dependent molecular chaperones that remodel and activate hundreds of client proteins with the assistance of cochaperones. In Escherichia coli, the activity of the Hsp90 homolog, HtpG, has remained elusive. To explore the mechanism of action of E. coli Hsp90, we used in vitro protein reactivation assays. We found that E. coli Hsp90 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
147
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(164 citation statements)
references
References 49 publications
(74 reference statements)
17
147
0
Order By: Relevance
“…Another upregulated protein is commonly reported as a stress response, namely, a heat shock protein (spot 335). Heat shock protein 90 (YP_001726093.1) participates in several cellular process, with protein folding and degradation being its chaperone roles (26). Proteins with other biological functions were also found to be differentially expressed (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Another upregulated protein is commonly reported as a stress response, namely, a heat shock protein (spot 335). Heat shock protein 90 (YP_001726093.1) participates in several cellular process, with protein folding and degradation being its chaperone roles (26). Proteins with other biological functions were also found to be differentially expressed (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…7A, the cyanobacterial DnaJ2 is homologous to the E. coli type II J-protein CbpA. It has been shown that CbpA is particularly effective in making DnaK function with HtpG (20). Thus, the type II J-protein may play a special role for the cooperative action of HtpG with DnaK.…”
Section: Discussionmentioning
confidence: 99%
“…The DnaK system consists of DnaK, GrpE, and DnaJ or CbpA. Their results suggest that the DnaK chaperone system acts first on the substrate protein, and then HtpG and the DnaK system function collaboratively to complete remodeling of the substrate (20).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand there is no doubt that protein disaggregation is an ATP-driven process [20]. For example, HtpG can interact with DnaK/DnaJ/GrpE to further promote refolding of aggregated proteins in an ATP-dependent manner [21]. Alternatively, ClpB can also assist in cooperation with DnaK/DnaJ/GrpE in ATP-driven refolding of aggregated proteins [20,22,23].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%